MASA DEPAN DAN ETIKA PROFESI PENEGAK HUKUM DI TENGAH ABAD MILINEAL - Hindun Umiyati; Supardin; Hamsir (CV. Ulil Albab Corp, 2022)
One aspect that is highlighted by ethics and morals regarding the behavior of a person's actions is in the field of expertise called profession. Due to the profession as a job about theoretical and technical expertise, which relies on honesty, the dependence and expectations of people who need help are very large in order to implement a good law enforcement system, therefore the bearers of a profession are required to meet certain conditions in carrying out and carrying out their duties. and professional functions, so that they really work professionally in their fields. This research can be categorized as normative juridical research. The type of data used is secondary data. Data collection in this study was carried out through a literature study. The data were analyzed in a qualitative normative manner. Law enforcement in Indonesia at this time should follow the applicable law and is expected to realize legal development. In addition, in accordance with Article 6 paragraph (1) of Law Number 12 of 2011 concerning the Establishment of Legislation, the formation of national law needs to be based on the principles of protection, humanity, nationality, kinship, archipelago, diversity in diversity, justice, equality in law and government, order and legal certainty, balance, harmony, and harmony. The principles for forming these laws and regulations deriving the noble values ​​of Pancasila as legal ideals / rechtsidee